Examining Authenticity: An Initial Exploration of the Suitability of Handwritten Electronic Signatures. (June 2017) - Heckeroth, J.; Boywitt, C.D.
Highlights: Electronic signatures' suitability for forensic examination is evaluated. Professional forensic handwriting examiners served as subjects. No general differences were found between electronic and paper–pen-signatures. Abstract: Considering the increasing relevance of handwritten electronically captured signatures, we evaluated the ability of forensic handwriting examiners (FHEs) to distinguish between authentic and simulated electronic signatures. Sixty-six professional FHEs examined the authenticity of electronic signatures captured with software by signotec on a smartphone Galaxy Note 4 by Samsung and signatures made with a ballpoint pen on paper (conventional signatures). In addition, we experimentally varied the name ("J. König" vs. "A. Zaiser") and the status (authentic vs. simulated) of the signatures in question. FHEs' conclusions about the authenticity did not show a statistically significant general difference between electronic and conventional signatures. Furthermore, no significant discrepancies between electronic and conventional signatures were found with regard to other important aspects of the authenticity examination such as questioned signatures' graphic information content, the suitability of the provided sample signatures, the necessity of further examinations and the levels of difficulty of the cases under examination. Thus, this study did not reveal any indications that electronic signatures captured with software by signotec on a Galaxy Note 4 are less well suited than conventional signatures for the examination of authenticity, precluding potential technical problems concerning the integrity of electronic signatures.